The Reliability and Validity of Gluteal Endurance Measures (GEMs) - B J Lehecka; Barbara S Smith; Todd Rundell; Thomas A Cappaert; Nils A Hakansson (International Journal of Sports Physical Therapy, 2021)
# Background